Linked frequency and intensity of persistent volcanic activity at Stromboli (Italy). Issue 13 (3rd July 2013) - Taddeucci, J.; Palladino, D. M.; Sottili, G.; Bernini, D.; Andronico, D.; Cristaldi, A.
Abstract : [1] Relationships between frequency and intensity of volcanic eruptions are actively sought by geophysicists for both monitoring and research purposes. By analyzing surveillance videos of persistent volcanic activity at Stromboli (Italy), we derived the frequency and jet height of >4000 explosions that occurred in 72 h‐long time windows sampled yearly from 2005 to 2009. We found a positive relationship linking explosion frequency and jet height (linked to eruption intensity) when averaging the two parameters over time intervals from hours to days, with a stronger correlation for longer intervals. We interpret this behavior as the response of the magmatic system to variable influx of magma and gas at depth, increased flux at depth causing more frequent and stronger explosions at the surface. This relationship entails concurrent control of source processes over explosion frequency and intensity, directly impacting modeling of explosion sources at persistently active volcanoes in general and hazard assessment at Stromboli in particular. Key Points: Tracking frequency and relative intensity of Strombolian explosions at Stromboli Frequency and intensity correlate positively when time‐averaged over hours‐days Rising input of magma/gas at depth raises both explosion frequency and intensity